S-adenosylmethionine affects ERK1/2 and STAT3 pathway in androgen-independent prostate cancer cells - Schmidt, Thomas (Molecular biology reports, 2022)
The most critical point in the treatment of prostate cancer is the progression towards a hormone-refractory tumour, making research on alternative therapies necessary. This study focused on the methyl donor S-adenosylmethionine (SAM), which is known to act as an antitumourigenic in several cancer cell lines. Though a genome-wide downregulation of proto-oncogenes in prostate cancer cell lines treated with SAM is obvious, the anticancer effects remain elusive. Thus, in this study, the impact of SAM treatment on the cell cycle, apoptosis and cancer-related pathways was investigated.
Gesehen am 06.02.2024